Practicality Analysis of PBL-Based Mathematics in Circle Material - Lestari, Puji; Mardiyana, Mardiyana; Slamet, Isnandar (Universitas Islam Negeri Raden Intan Lampung, 2020)
This study aims to analyze the practicality level of the PBL-based mathematics module on circle material. The practicality analysis of the developed mathematics module aimed to determine the ease of use of the module according to teachers and students. This research is a qualitative descriptive study. A practicality questionnaire was used to collect the data. The subjects in this study were 2 mathematics teachers and 13 grade VIII students at SMPN 2 Jumapolo. The results of the analysis showed that the average of total score of the teacher practicality questionnaire was 78.15 and could be stated as practical. The average score of the student practicality questionnaire was 74.87, could be stated as practical. Based on the results of the analysis of the teacher and student practicality questionnaires, it can be concluded that the mathematics module based on problem-based learning on circle material is considered practical and can be used in mathematics learning.